Answer:
24
Step-by-step explanation:
5^2-3^2=?
25-9=16
sqrt 16 = 4
6×4=24
Answer:
x=-2, y=-6
Step-by-step explanation:
Simple substitution.
Since y is isolated in one of the equations already, you can plug it into the second equation.
x - 2(3x) = 10
x - 6x = 10
-5x = 10
x = -2
Sub. x = -2 into 3x = y:
3(-2) = y
y = -6
total of ages now is 67 + 4 + 4 = 75
S=shelly
M= Michelle
Michelle is 3 yrs younger than Shelly so use S-3
S +M = 75
replace M with S-3 to get:
S +S-3=75
2S=78
s=39
So shelly is 39
Michelle is 3 years younger = 39-3 = 36
Answer:
1% of 4000 + 4% of B = 2% of (4000 + B)
40 + 0.04*B = 0.02( 4000 + B)
40 + 0.04* B = 80 + 0.02*B
40 + 0.04*B - 80 - 0.02B = 0
0.02*B - 40 = 0
0.02*B = 40
2B = 4000
B = 2000
Step-by-step explanation: